Floor Cleaning Robot - Joshi, Mansi Ramesh; Pawar, Shraddha Dilip; Sable, Vrushali Bandu; Waghmare, Madhavi (Indian Journal of Computer Science, 2021)
The cleaning robot takes significant place in automated examination. Floor cleaning robot is utilized in indoor spots like rooms, enormous workplaces etc. Cleaning physically is troublesome and dreary work and there is chance that the person cleaning leaves some part messy. Furthermore, it is tedious and bothering. The cleaning activity is more mechanized and therefore, the cleaning robot helps people. The robot is in small in size and is lightweight, so it can be used in a packed spot. Enormous workplaces have huge cleaning requirements, and physically it is not productive. Robots are advantageous for this reason.